Smoking at the workplaces in Italy after the smoking ban in the Lazio Region - Ruscitti, Luca Enrico; Castellani, Fulvio; La Torre, Giuseppe; De Giusti, Maria; Dominici, Fabio; Valente, Pasquale (La Medicina del Lavoro, 2021)
Background: In Italy, an anti-smoking law was issued in 2003, with the aim of reducing tobacco smoking inside public places. Objectives: The aim of the study was to assess the observance of the smoking ban in Italy, during the period 2010-2014, in several workplaces and to evaluate the perception of workers, both smokers and non-smokers, on this issue. Methods: This cross-sectional study analyzed data resulting from a self-administered questionnaires in 59 companies, from several working sectors (transport, healthcare and building), in the Latium Region in Italy. Results: Out of 7200 questionnaires, 6996 were included in the analysis: 43.7% of the employees think that the smoking ban is respected in the workplace; women are more prone to think that the ban is not observed. Smokers tend to perceive the ban to be respected (AOR: 0.69; 95% CI: 0.62-0.77) while non-smokers feel more exposed to second-hand smoke (AOR: 1.57; 95% CI: 1.39-1.77). Workers in intellectual and highly specialized professions (AOR: 1.63; 95% CI: 1.25-2.13), technical professions (AOR: 1.64; 95% CI: 1.28-2.10) and craftsmen, skilled workers and farmers (AOR: 1.42; 95% CI: 1.09-1.85) tend to perceive the smoking ban not to be observed and the last two classes are the ones who feel the most exposed to second-hand smoke (AOR: 6.68; 95% CI: 0.50-0.90; AOR: 0.52; 95% CI: 0.38-0.70). Discussion: The results of this study can be used as a starting point for the implementation of new strategies to reduce tobacco addiction, beginning from the compliance with the ban on smoking in the workplace and the promotion of a healthy lifestyle.